Discarding the Barthian Spectacles: Part I, Recent Scholarship on the History of Early 20th Century German Protestant Theology - Aune, Michael B. (Dialog, 2004)
This essay introduces “the veritable renaissance” of scholarly attention devoted to the theologies of the early twentieth century. This “renaissance” challenges us to discard the “Barthian spectacles” through which we have been reading the theological history of this time and to examine more closely the complex context—social, political, churchly, cultural—in which theology was done.